Proposal for a simulator for a higher professional research course in distance mode - Goncalves, Daniele Assad; De Medeiros, Luciano Frontino; Moser, Alvino (Seven Editora, 2023)
A proposal for a professional simulator is presented to be applied as a learning activity in a higher course of technology in professional research. Through the simulation of cases based on reality, students can align theoretical knowledge with the personal day-to-day experimentation of a private detective. The game experience seeks to mix the entertainment and education proper of games with an educational item. Based on the premises and a storyboard process, the game is developed in a way to simulate random experiences, linked to real problems, and provides a challenging level in a way to maintains an experience of flow on the student’s part. DOI: https://doi.org/10.56238/devopinterscie-088